Manobras de recrutamento alveolar em indivíduos com síndrome do desconforto respiratório agudo: uma revisão da literatura - Cássia Ferreira Santos (2011)
Introduction: The alveolar recruitment maneuvers are used in mechanical ventilation strategies in order to promote the opening of collapsed alveoli. In acute respiratory distress syndrome, such a maneuver is performed in order to increase the area available for pulmonary gas exchange, and thus promote arterial oxygenation. Aim: To review the scientific literature on narrative in alveolar recruitment techniques used for the treatment of ARDS. Methods: We performed a query on the databases Pubmed, Scielo, Lilacs, and books and scientific journals. Were included in search scientific articles from 2000 to 2011, published in full in English and Portuguese, whose research focus mechanically ventilated patients suffering from ARDS who underwent alveolar recruitment maneuvers. Were excluded prior to 2000 scientific papers published in languages other items that were unrelated to the subject matter, incomplete texts, and studies directed specifically to acute lung injury. Results: Forty-two were selected to achieve the revised narrative in question, and fourteen approached the MRA as a therapeutic technique in ARDS / ARDS. Of these, five investigated the use of PCV and VCV in five other ARM, three studies have addressed the prone position and found a job as the effect of CPAP mode choice in the MRA. Conclusion: Alveolar recruitment techniques commonly used in MRA in patients with ARDS / SARA are: firstly the use of PCV and VCV as ventilatory mode, followed by the prone position, and finally the CPAP. According to this review the MRA have proved safe in the treatment of patients with ARDS / ARDS.